PEMBENTUKAN HABITUS MASYARAKAT SUKU DAYAK BENUAQ PADA RITUAL BELIATN SENTIU DI KESULTANAN KUTAI KARTANEGARA ING MARTADIPURA - Yofi Irvan Vivian; Muhammad Bahri Arifin; Ian Wahyuni (Institut Seni Indonesia Surakarta, 2022)
Beliatn Sentiu is used by the Benuaq Dayak people as a non-medical treatment. This is because, The Beliatn Sentiu process uses offerings and mantra readings (bememang). The purpose of this study is to determine the musical characteristics of one of the music played and the formation of habitus that occurs in the Dayak Benuaq tribe in the Beliatn Sentiu Ritual process in Kutai Ing Martadipura. Research Methods The research methods used are Qualitative. This research also uses the approach of field research methods by Bruno Nettl, namely desk work and field work. Pemeliatn is the dominant agent, while Pengugu, Penu'ung, and Rotatn are the dominating agents. This is because Pemeliatn has a large capital, especially in cultural and social capital. The interaction of these two capitals forms a symbolic capital so that in The Beliatn Sentiu Ritual, the command of the Pemeliatn is always followed by The Pengugu, Penu'ung, and Rotatn. The beliefs of the Dayak Benuaq people are influenced by ancestral spirits and supernatural realms, making habitus constructed in the Beliatn Sentiu Ritual. The Beliatn Sentiu process is believed to be the help of ancestral spirits in healing. This is what makes the Beliatn Sentiu still carried out today.